Analisis Kadar Flavonoid pada Kulit Buah Alpukat (parsea americana Mill.) yang Beredara Di Pasar Inpres Palu - Aprilianti Pauner; Baharuddin Hamzah (Universitas Tadulako, 2022)
Avocado (Parsea americana Mill) is a fruit that can grow in tropical and subtropical areas. Avocado (Parsea americana Mill) has a delicious taste so it is favored by many Indonesian people. This study aims to determine the levels of flavonoids in the skin of long green avocados, round green avocados and round red avocados. Avocado peel powder is extracted by maceration. The solvent used is ethanol solvent. The standard solution used was quercetin standard solution with various concentrations of 5%, 20%, 40%, 60%, 80% and 100%. Determination of total flavonoid levels using UV-Vis spectrophotometry with a wavelength of 431 nm. The results showed that the levels of flavonoids in the long green avocado skin were 1614,286 mg/100g, round green avocado 1340,476 mg/100g and round red avocado 1385,714 mg/100g.